Executive development: meeting the needs of top teams and boards - Jackson, Sheila; Farndale, Elaine; Kakabadse, Andrew P. (Emerald Group Publishing Limited, 2003)
In a review of the literature, supported by six case studies, executive development for senior managers in public and private organisations is explored in depth. The study looks at the roles and responsibilities of the chairman, CEO, executive and non-executive directors, the required capabilities to achieve successful performance, and the related executive development activity implemented to support these. Methods of delivery, development needs analysis and evaluation are explored in case organisations to ascertain current practice. A detailed review of the leadership and governance literatures is included to highlight the breadth of knowledge required at director level. Key findings of the study include the importance of focusing executive development on capability enhancement, to ensure that it is supporting organisational priorities, and on its thorough customisation to the corporate context. Deficiencies in current corporate practice are also identified.
Keywords: Development; Executives; Governance; Leadership; management